Royal College of Obstetricians and Gynaecologists guidelines: How evidence-based are they?. (November 2014) - Prusova, K.; Churcher, L.; Tyler, A.; Lokugamage, A. U.
Abstract Evidence-based medicine aims to translate scientific research into good medical practice. The Royal College of Obstetricians and Gynaecologists publishes recommendations and guidelines to guide clinicians in decision-making. In this study, the evidence base underlying the 'Green-top Guidelines' has been analysed in order to establish the quality of research underlying recommendations. During this descriptive study of 1, 682 individual recommendations, the authors found that only 9–12% of the guidelines were based on the best quality (Grade A) evidence. The authors believe that this type of analysis serves to provide greater clarity for clinicians and patients using guidelines and recommendations in the field of obstetrics and gynaecology to make collaborative clinical decisions.